Análisis a los estados financieros de la cooperativa de ahorro y crédito “san miguel de los bancos” Ltda. en el cantón San Miguel de los Bancos, provincia de Pichincha, periodo 2013 – 2014 - Medina Pasaca, Martha Cecilia (2016)
The thesis entitled: ANALYSIS OF THE FINANCIAL STATEMENTS OF THE COOPERATIVE OF SAVINGS AND CREDIT, "SAN MIGUEL DE LOS BANCOS", IN COUNTY OF SAN MIGUEL DE LOS BANCOS, PICHINCHA PROVINCE, PERIOD 2013 - 2014, Developed to meet the prerequisite for the category of Engineer in Accounting and Auditing Public Accountant, the main objective is to apply financial analysis reflecting the real situation of the operative during the two periods under study, using analytical methods and financial indicators. To meet the objective of assessing the financial situation of the cooperative we proceed to perform vertical and horizontal analysis allowed to measure the degree of representativeness of each account before the group to which it belongs, as well as determine the degree of variation of the asset were determined by the presented assets, liabilities of the balance sheet and the variation of expenditures, income and surplus for the year in the income statement. We fulfilled the application with the financial indicator system, PERLAS, which shows that the cooperative has a good level of economic and liquid solvency. The profit margin shows signs of moderate increase the graphical representation of the results were performed and the report describes the elaborated institutional strengths and weaknesses. In the final analysis we observe that the entity is in a normal financial and economic state. It is necessary to take certain actions of change with intent to reduce the margin of delinquency, the debt level, the percentage of non-performing assets and operational expenses always trying to improve and strengthen the management as well as boost growth and profitability of each fiscal year of the cooperative of savings and credit.